Validation of a Web-Based, Time-Use Application to Assess Children’s School Meal Intakes: My E-Diary for Activities and Lifestyle (MEDAL) - Sarah Yi Xuan Tan (MDPI AG, 2021)
My E-Diary for Activities and Lifestyle (MEDAL), a web-based application, was developed to assess the diets of children. This study examined the validity of school recess meals reported by children on MEDAL, using meal photography as the reference. Recess meals were photographed by trained researchers, and food items and portion sizes of recess meals reported on MEDAL were compared to recess meal photos. Validity was assessed by percentages of match, omission and intrusion for food items and percentages of the match, underestimation and overestimation for portion sizes. The Mann–Whitney test and the Wilcoxon matched-pairs signed-rank test examined if sex, school and day of recording influenced the validity of food item reporting. We found that participants (n = 33, aged 10–11 years) recalled 60.2% of food items consumed at recess accurately (matches); omissions (24.6%) were more common than intrusions (15.2%). Omissions tended to be side dishes, and intrusions tended to be high-calorie items. Sex, school and day of recording did not influence validity. For food portion sizes, 58.3% of items were accurately reported. Overestimations (33.3%) were more common than underestimations (8.3%). In conclusion, these children were able to report food items consumed during school recess meals using MEDAL, albeit with limitations on the degree of accuracy.